An Energy Control and Management System forUrban Rail Transit - LI Hongbo; ZHANG Chao; HUANG Zihao; WANG Xiong; LUO Wenguang; ZHANG Zhixue (Kongzhi Yu Xinxi Jishu)
With the rapid development of rail transit, issues of a large amount of energy consumption, serious emission and so forth are increasingly the focus of social attention. To enhance the energy usage efficiency of the overall traction power system, this paper proposes an energy control and management system for urban rail transit. This system employs wireless 4G modules to obtain the instantaneous power and positions of trains, parameters of traction power system, real-time status of the substations and bidirectional converters. Based on the above data, digital reconstruction of real traction power system is achieved by iteratively calculating space matrix. Considering the objective functions and system physical limitations, the energy control and management system optimizes DC output voltage commands of bidirectional converters through heuristic algorithms based on the digital reconstructed traction power system. Consequently, power flow dispatching of the entire metro line is realized and make the metro traction power system have a better power supply quantity and a higher efficiency. According to the on-site experiments conducted in an actual metro line of a certain city, the overall system efficiency is increased by 0.767%, which verifies the effectiveness of the proposed energy control and management system.